2018
DOI: 10.3389/fmicb.2018.02761
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals Common and Specific Responses of a Marine Diatom Thalassiosira pseudonana to Different Macronutrient Deficiencies

Abstract: Macronutrients such as nitrogen (N), phosphorus (P), and silicon (Si) are essential for the productivity and distribution of diatoms in the ocean. Responses of diatoms to a particular macronutrient deficiency have been investigated, however, we know little about their common or specific responses to different macronutrients. Here, we investigated the physiology and quantitative proteomics of a diatom Thalassiosira pseudonana grown in nutrient-replete, N-, P-, and Si-deficient conditions. Cell growth was ceased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 88 publications
4
27
1
Order By: Relevance
“…The mitochondrial AOX protein used for removing an excess electron in the nutrient-limited diatom (Allen et al, 2008) and upregulation of this protein could be involved in the mitigation of mitochondrial ROS production (Lin et al, 2017) in temperature-limited cells, whereas downregulation of this AOX protein and many other essential enzymes of the FoF1-type proteins in S. dohrnii suggests the regulation of ATP production with a coincident blockage of the respiratory chain under Si limitation. Consistent proteomic regulation was seen earlier on diatoms and cyanobacteria responding to a lower temperature (Mackey et al, 2013;Dong et al, 2016) and Si concentration (Chen et al, 2018;Thangaraj et al, 2019). Taken together, in S. dohrnii PSII, linear electron flow (grana) to NADPH mechanisms could be regulated by (Si) concentration, whereas PSI, LHC, and cyclic electron flow (stroma) to ATP metabolisms could be modulated by temperature limitation.…”
Section: Specific Cellular Response In Photosynthesis and Associated supporting
confidence: 77%
See 3 more Smart Citations
“…The mitochondrial AOX protein used for removing an excess electron in the nutrient-limited diatom (Allen et al, 2008) and upregulation of this protein could be involved in the mitigation of mitochondrial ROS production (Lin et al, 2017) in temperature-limited cells, whereas downregulation of this AOX protein and many other essential enzymes of the FoF1-type proteins in S. dohrnii suggests the regulation of ATP production with a coincident blockage of the respiratory chain under Si limitation. Consistent proteomic regulation was seen earlier on diatoms and cyanobacteria responding to a lower temperature (Mackey et al, 2013;Dong et al, 2016) and Si concentration (Chen et al, 2018;Thangaraj et al, 2019). Taken together, in S. dohrnii PSII, linear electron flow (grana) to NADPH mechanisms could be regulated by (Si) concentration, whereas PSI, LHC, and cyclic electron flow (stroma) to ATP metabolisms could be modulated by temperature limitation.…”
Section: Specific Cellular Response In Photosynthesis and Associated supporting
confidence: 77%
“…Nitrate is often mentioned to limit diatom growth in the ocean because of its contribution to binding chlorophyll, amino acids, and nucleic acids. Earlier proteomic observation on diatoms showed that limitation of iron, phosphate, and silicate has a coupling effect with N transporters, leading to downregulated nitrate transporters and their assimilation (Nunn et al, 2013;Chen et al, 2018). Similarly, many downregulations of nitrate transporters observed in this study responded to Si deficiency (Table 1), indicating lower nitrate assimilation (Figure 1) and cellular N quota (Figure 1).…”
Section: Specific Cellular Nutrient Assimilationsupporting
confidence: 68%
See 2 more Smart Citations
“…There are a growing number of studies taking advantage of proteomics to study diatom responses to stress, e.g. Muhseen et al (2015) or Chen et al (2018). Proteomics approaches have been used successfully in Viridiplantae to identify candidates for thioredoxin interactions (Montrichard et al, 2009;Perez-Perez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%